Reliability of tachycardia as an early warning sign in acute clozapine-induced cardiac inflammation: Protocol for a systematic review - James Richard O’Neill; Prakruti Babu Narendra Prasad; Matthew Croft; Matthew Manton; Natalie King; Daniel Romeu (PLoS ONE, 2026)
Introduction Clozapine-induced cardiac inflammation (CICI) can have serious consequences for people with psychosis and can be fatal if not detected in a timely manner. The best available methods of investigation for CICI are resource-intensive, whereas clinical practice often utilises cheaper and more practical methods of detection such as history, examination, and blood tests. Heart rate monitoring is commonly used as an early-warning sign in detecting potential CICI. Previous studies have found that, although this has a high sensitivity, it has poor specificity. As far as we are aware, no systematic review has investigated the role of tachycardia as a detection tool for CICI. Methods and analysis Systematic diagnostic test accuracy review of the available literature will be used to assess the effectiveness of tachycardia as an early-warning sign for CICI. We will search eight electronic databases and grey literature using a comprehensive and systematic approach. Grey literature sources will include conference proceedings and professional guidance documents identified through expert consultations. Retrieved articles will be critically appraised, synthesised, and meta-analysed, where data permit. Ethics and dissemination This systematic review will use data from existing studies, hence no ethical approvals are required. Findings will be disseminated to academic colleagues through a peer-reviewed publication and relevant academic meetings, and to clinicians through distribution to local and national clinical networks. PROSPERO registration ID: CRD42025650379